Photoluminescence: Ultrafast and Robust UV Luminescence from Cu‐Doped ZnO Nanowires Mediated by Plasmonic Hot Electrons (Advanced Optical Materials 6/2016). Issue 6 (June 2016) - Huang, Xiaohu; Chen, Rui; Zhang, Chen; Chai, Jianwei; Wang, Shijie; Chi, Dongzhi; Chua, Soo Jin
Abstract : Leveraging on plasmonic hot electrons is an emerging strategy for electron–hole separation towards efficient photovoltaics and photocatalysis. On page 960, X. Huang, S. J. Wang, S. J. Chua, and co‐workers extend this concept to electron–hole recombination for illumination, which is rarely reported. By taking advantage of the good energy match between the dopant‐correlated green luminescence in Cu‐doped ZnO nanowires and the localized surface plasmon resonance of Au nanoparticles, an intense, ultrafast, and temperature‐robust UV luminescence is achieved in the nanowires after coating with Au nanoparticles.